Optimization Of Legal Aid Institution Functions in Regards Nominee Agreement Through Civil Law And Criminal Law Perspektif In Tibubiu-Tabanan Village - I Gusti Agung Ayu Gita Pritayanti Dinar; I Nyoman Gede Sugiartha; Ni Made Puspasutari Ujianti; I Made Ardena; I Kadek Wahyu Dwipayana; Putu Marita Maharani Putri (Community Service Journal of Law, 2024)
Most villages in Bali have characteristics of "Tri Hita Karana" and "Sad Kerthi" as philosophical local wisdom values. In this case, these characteristics may be used as philosophical and sociological pillars in implementing regional investment with the ultimate ending being community welfare in line with the spirit of Pancasila as the ground norm for every legal regulation in Indonesia. Community service activities should be carried out by conveying various information in the field of legal science by providing legal counseling and consultation to the community in various areas of life in the fields of civil and criminal law. One of the thing that should be concern to is the understanding of legal science to the environment in Tibubiu Village, with this legal counselling program so most every part of Tibubiu village will get more knowledgement about nominee agreement as borrowing a name based on a statement or power of attorney made by both parties, as tends to be exploited by foreign nationals using the name of an Indonesian citizen to be included as the land owner on the certificate. In order to increase knowledge and find solutions to the matters caused by nominee agreements, efforts need to be made to convey more in-depth and consistent information regarding the impact of using nominee agreements. Through this community service, the people of Tibubiu village can find out and describe the impact of the use of nominee agreements.